Civilizational Problem or Political Crisis? Comparative Analysis of Mālek Bennabi and Syed Mawdūdī’s Approach to Renaissance - Malik, Bilal Ahmad (Journal of Islamic Thought and Civilization, 2022)
After having reached the stage where Islamic civilization delivered optimum, it started declining. Nevertheless, in different epochs of Islamic history, some remarkable personalities emerged reclaiming the functionality of iḥyā; i.e., the renaissance principle. In the contemporary times, Mālek Bennabī and Syed Mawdūdī have phenomenally contributed to the Muslim renaissance discourse. Both of them have critically examined the pathology of jumūd; i.e., the tendency of stagnation in the Muslim world. Although, they identified similar causes and symptoms, nevertheless, having lived in different socio-political contexts, they came up with certain methodological differences in their approach. Both the scholars developed a systematic response suggesting a way forward–the method of renaissance. In Bennabī’s discourse, the pathology is fundamentally civilizational, i.e., crisis in the civilizational equation between man, soil and time. While in Mawdūdī’s discourse, the pathology is fundamentally political; i.e., crisis in the nature of political relation between state, society and religion. Against this backdrop, the paper aims to present following points. First, the paper presents a brief analysis of Bennabī’s civilizational approach and Mawdūdī’s political approach in order to understand their scheme of thought while engaging with the question of jumūd and iḥyā. Second, the paper juxtaposes the three key concepts namely civilization, religion, and revival used by both Bennabī and Mawdūdī in their theoretical elaborations to outline the differences and similarities in their method of analysis. Keywords: Islam, Decline, Renaissance, Civilizational Approach, Political Approach